2024
DOI: 10.1039/d4sc01074d
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed atroposelective synthesis of C–O axially chiral compounds enabled by chiral 1,8-naphthyridine based ligands

Lei Dai,
Xueting Zhou,
Jiami Guo
et al.

Abstract: A copper-catalyzed atroposelective construction of C–O axially chiral compounds using novel 1,8-naphthyridine-based chiral ligands was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…In the competitive field of atroposelective synthesis of axially chiral diaryl ethers, Gao and Yao, [40] on one hand, and Lu, [41] on the other, have successively reported approaches starting from dialkynes 58 using the Copper Alkyne-Azide click Cycloaddition (CuAAC) strategy with simple azides in the presence of chiral oxazoline ligands L2 or L3 (Scheme 16). [42] Mechanistically and in both cases, this reaction involves a sequential enantioselective desymmetrization-kinetic resolution leading to axially chiral triazolodiaryl ethers 59 in excellent yields and enantioselectivities when at least one ortho-substituent (R 3 ) is a bulky tert-butyl or tert-pentyl group, while adamantyl or isopropyl gave much lower enantioselectivity and a racemic compound is obtained with an ethyl.…”
Section: Aryl Ethersmentioning
confidence: 99%
“…In the competitive field of atroposelective synthesis of axially chiral diaryl ethers, Gao and Yao, [40] on one hand, and Lu, [41] on the other, have successively reported approaches starting from dialkynes 58 using the Copper Alkyne-Azide click Cycloaddition (CuAAC) strategy with simple azides in the presence of chiral oxazoline ligands L2 or L3 (Scheme 16). [42] Mechanistically and in both cases, this reaction involves a sequential enantioselective desymmetrization-kinetic resolution leading to axially chiral triazolodiaryl ethers 59 in excellent yields and enantioselectivities when at least one ortho-substituent (R 3 ) is a bulky tert-butyl or tert-pentyl group, while adamantyl or isopropyl gave much lower enantioselectivity and a racemic compound is obtained with an ethyl.…”
Section: Aryl Ethersmentioning
confidence: 99%
“…In the competitive field of atroposelective synthesis of axially chiral diaryl ethers, Gao and Yao, [40] on one hand, and Lu, [41] on the other, have successively reported approaches starting from dialkynes 58 using the Copper Alkyne-Azide click Cycloaddition (CuAAC) strategy with simple azides in the presence of chiral oxazoline ligands L2 or L3 (Scheme 16). [42] Mechanistically and in both cases, this reaction involves a sequential enantioselective desymmetrization-kinetic resolution leading to axially chiral triazolodiaryl ethers 59 in excellent yields and enantioselectivities when at least one ortho-substituent (R 3 ) is a bulky tert-butyl or tert-pentyl group, while adamantyl or isopropyl gave much lower enantioselectivity and a racemic compound is…”
Section: Minireviewmentioning
confidence: 99%
“…The synthesis of such compounds, however, is challenging because of their complex biaxial structures, low rotational barriers, and the precise steric interactions required. Since Fuji et al’s initial study on C–O axial diaryl ethers, there have been several examples of their construction via asymmetric catalysis. Zhong and Zeng et al recently described a chiral phosphoric acid (CPA)-catalyzed dynamic kinetic resolution of dicarbaldehydes with anilines to afford C–O axially chiral diaryl ethers through asymmetric hydrogen transfer . Subsequently, Yang et al demonstrated CPA-catalyzed electrophilic aromatic aminations of 2-aryloxy-1,3-benzenediamines with azodicarboxylates .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Biju group, the Ye group, the Zhang group, and the Gao group have independently reported N -heterocyclic carbene (NHC)-catalyzed atroposelective esterification of dialdehyde-containing diaryl ethers . The Gao and Yao group and the Lu group represented a copper-catalyzed enantioselective click reaction between bisalkynes and azides to construct axially chiral diaryl ethers . During the submission of the manuscript, the Yu and Li group developed a cobalt-catalyzed photoreductive coupling of dialdehyde and alkyne, which afforded diaryl ethers containing axial and central chirality .…”
Section: Introductionmentioning
confidence: 99%